2018
DOI: 10.1016/j.ssresearch.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Labour market entries and exits of women from different origin countries in the UK

Abstract: In the context of increasing women's labour force participation (LFP) across Western countries, there remain large differences in LFP for women of different ethnic origins.While existing research has demonstrated that part of these differences can be attributed to compositional differences (age, qualifications, family context etc.) and to differences in gender role attitudes and religiosity, residual 'ethnic effects' typically remain. Further insight into the drivers of such differences has the potential to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 71 publications
3
46
0
13
Order By: Relevance
“…It is possible that this group is comprised of ethnic or religious groups that espouse traditional gender norms. We have not investigated ethnicity or religious affiliation as part of this study, but others have shown ethnic variation in women's employment in this data set (Khoudja & Platt, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this group is comprised of ethnic or religious groups that espouse traditional gender norms. We have not investigated ethnicity or religious affiliation as part of this study, but others have shown ethnic variation in women's employment in this data set (Khoudja & Platt, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a vast body of migration research has examined objective indicators of immigrants' integration (see Van Tubergen et al, 2004 for comparative research; Kogan, 2006Kogan, , 2007Heath and Cheung, 2007;Heath et al, 2008 for a review; Fleischmann and Dronkers, 2010;Gorodzeisky and Semyonov, 2017;Khoudja and Platt, 2018 for recent research), immigrants' subjective evaluation of their life situation is far less studied. Recent years have, however, witnessed a growing interest in immigrants' own assessments of their lives in host societies, captured by individual life satisfaction (see Hendriks, 2015 for a review; Baykara-Krumme and Platt, 2018; Hendriks and Bartram, 2018;Kogan et al, 2018 for recent research).…”
Section: Introductionmentioning
confidence: 99%
“…However, differences with respect to the majoritarian native population remain. This is especially the case for some groups, like Turkish groups in Germany (Diehl, Koenig, and Ruckdeschel 2009) and Pakistanis and Bangladeshis in the UK (Khoudja and Platt 2016). Current figures for the UK (based on the data used in this study) suggest that most ethnic minority groups, but especially Pakistanis and Bangladeshis, continue to hold, on average, more traditional views than white UK individuals (i.e.…”
Section: Introductionmentioning
confidence: 70%
“…Most importantly, one of the main concerns behind the persistence of traditional gender role views is its effects on women. Such views have been found to play a negative role in women's educational and labour market opportunities (Davis and Greenstein 2009; Khoudja and Fleischmann 2015;Khoudja and Platt 2016).…”
Section: Introductionmentioning
confidence: 99%